Strengthening the 3C Partnership for Sustainable District - Chanita Rukspollmuang; Pornchai Mongkhonvanit; Trithos Kamsuwan; Narumol Aungsirisak; Jaratdao Reynolds (Journal of Sustainability Perspectives, 2025)
A mutual relationship among the 3C partners—Campus, City, and Community—is essential for achieving the Sustainable Development Goals (SDGs). Siam University, as the only higher education institution in the Phasi Charoen district, has been actively collaborating with surrounding communities and the district office for several years. At present, university administrators and faculty members have taken leading roles in supporting local and community development. The UPC4LocalSDGs and the 4Co (Co-Create, Co-Design, Co-Produce, Co-Reflect) Action Model have been developed as a framework for working with the district office and communities, which serve as our social living labs. This paper presented case studies that employed the 4Co action model in the 3C partnership sustainable initiatives. The “Tiny Heroes, Global Saviors” project in Lad Pachi community exemplified an innovative organic waste management approach using black soldier fly larvae to decompose organic waste and develop into a protein-based and laboratory-tested pet food product. The project received the 2024 IGGA Award in the “Benefitting Society” category. In the area of sustainable transportation, the “S-Guard Barrier Pole” was developed to enhance pedestrian safety, particularly for individuals using wheelchairs, while also deterring motorcyclists from driving on the footpath. Most recently, the 3C partners have co-developed a smart, rechargeable electric garbage-collection motorcycle designed for narrow alleys, with prototypes currently being tested in several communities throughout the district.